All-fibre dual-wavelength thulium-doped fibre laser based on spatial filtering effect - Azooz, S. M; Hamida, Belal Ahmed; Khan, Sheroz; Eltaif, Tawfig; Jasim, Ali Abdulhadi; Ahmad, Harith B.; Harun, Sulaiman Wadi (Institute of Physical Optics, 2014)
We report a room-temperature all-fibre dual-wavelength thulium-doped fibre laser that operates around 1900 nm and uses a spatial mode-beating filter in a ring configuration. By pumping the gain medium with an 800 nm laser and controlling the phase mismatch at the splicing points of a thulium-doped fibre, the two output lines are obtained at 1844.8 and 1852.0 nm, with the corresponding signal-to-noise ratios of 30 and 21 dB. The threshold pump power is 109.3 mW. At the maximum pump power of 131.7 mW, the output powers are 0.297 and 0.038 mW for the 1844.8 and 1852.0 nm laser lines, respectively.